Less is more: the 5Q approach - Jarvis, Andy; Eitzinger, Anton; Koningstein, Manon; Benjamin, Tenesia; Howland, Fanny C.; Andrieu, Nadine; Twyman, Jennifer; Corner-Dolloff, Caitlin (International Center for Tropical Agriculture, 2015)
Large agricultural development projects often struggle to achieve impact because they lack costeffective systems for capturing regular feedback from implementers and beneficiaries. Even when they use a participatory approach, they cannot easily take into account a large range of farmers’ needs and make them specific. The 5Q approach makes monitoring, evaluation and impact assessment of development projects significantly easier. It can also help to achieve impact. In Phase 1, we showed how 870 farmers can provide actionable feedback in just 15 minutes at a cost of 25 cents per farmer.